2017
DOI: 10.1097/md.0000000000007804
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of posterior cage migration following decompression and instrumented fusion for degenerative lumbar disorders

Abstract: The aim of this study was to explore the incidence and risk factors for posterior cage migration (PCM) following decompression and instrumented fusion for degenerative lumbar disorders, and hope to provide references in decision making and surgical planning for spine surgeons.By retrieving the medical records from January 2011 to December 2015, 286 patients were retrospectively reviewed. According to the occurrence of PCM, patients were divided into 2 groups: PCM group and non-PCM (N-PCM). To investigate risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 17 publications
1
33
0
1
Order By: Relevance
“…The prevalence of PCM was 2.52%, and one fourth of the patients (6 of 24) received revision surgery due to severe symptoms. The incidence was compatible to prior studies that reported the prevalence of PCM after TLIF or PLIF ranging from 1.17 to 14.7%, and occurred within 7 months after operation [3, 4, 6, 10]. Most cases of PCM occurred in the early postoperative period before achieving solid fusion.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The prevalence of PCM was 2.52%, and one fourth of the patients (6 of 24) received revision surgery due to severe symptoms. The incidence was compatible to prior studies that reported the prevalence of PCM after TLIF or PLIF ranging from 1.17 to 14.7%, and occurred within 7 months after operation [3, 4, 6, 10]. Most cases of PCM occurred in the early postoperative period before achieving solid fusion.…”
Section: Discussionsupporting
confidence: 89%
“…The authors failed to demonstrate the relationship between PCM and posteriorly located cages, possibly due to the small sample size. This current study had more patients compared to Aoki et al (24 patients versus 4 patients) and other existing literatures [3, 4, 68, 10]. Because the cages used in this study were all radiolucent, it was difficult to define cage margins by radiograph as Aoki et al did.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, other authors reported similar results. Li et al [20] and Lee et al [21] showed that lower BMD could result in cage migration. Pan et al [22] and Lee et al [23] reported that BMI of patients with cage retropulsion was higher than that in those without.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased PVM CSA is a risk factor for post-operative pedicle screw loosening (46). One study reported the correlation between pre-operative PVM degeneration and cage displacement after fusion (47). Reduced PVM strength and an increased pre-operative FIA may lead to proximal junctional kyphosis (48).…”
Section: Cross-sectional Area Difference Indicesmentioning
confidence: 99%